The Discovery of New Antilisterial Proteins From Paenibacillus polymyxa Kp10 via Genome Mining and Mass Spectrometry - Mokhtar, Nur Fadhilah Khairil; Hashim, Amalia Mohd; Hanish, Irwan; Zulkarnain, Aisyah; Raja Nhari, Raja Mohd Hafidz; Abdul Sani, Asmahani Azira; Abbasiliasi, Sahar; Ariff, Arbakariya; Mustafa, Shuhaimi; Rahim, Raha Abdul (Frontiers in Microbiology, 2020)
Abstract Inhibitory activity of antimicrobial protein against food-borne pathogen such as Listeria monocytogenes offers wide benefits for potential application in food and medical industries. However, various physicochemical properties and complexity of foods demands for discovery of new antimicrobial protein especially from newly isolated bacterial strain. We have previously obtained an unidentified pure bacterial culture originated from milk curd with excellent antilisterial activity. Here, we aim to identify the pure bacterium exerting the antilisterial activity and determine potential antimicrobial proteins through genome mining and mass spectrometry analysis. The analysis of the draft genome sequence identified the isolate as Paenibacillus polymyxa Kp10, and predicted biosynthetic gene clusters for paenibacillin, paenilan, paeninodin, sactipeptides, and thiazole-oxazole modified microcin encoded in its genome. Interestingly, nanoLC-MS/MS analysis instead revealed histone-like DNA binding protein HU, translation initiation factor IF-1 and 50S ribosomal protein L29 in the active fractions of P. polymyxa Kp10 that exhibiting the antilisterial activity. The antilisterial activity of the four proteins was verified through heterologous protein expression and antimicrobial activity assay in vitro. This study has identified structural regulatory proteins from Paenibacillus possessing antilisterial activity with future potential application in food and medical industries.